2012
DOI: 10.1590/s0100-736x2012000800002
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and detection of mecA and blaZ genes in coagulase-negative Staphylococcus isolated from bovine mastitis

Abstract: Pesq. Vet. Bras. 32(8) The present study evaluated the pheno-and genotypical antimicrobial resistance proϐile of coagulase-negative Staphylococcus (CNS) species isolated from dairy cows milk, specially concerning to oxacillin. Of 100 CNS isolates, the S. xylosus was the prevalent species, followed by S. cohnii, S. hominis, S. capitis and S. haemolyticus. Only 6% were phenotypically susceptible to the antimicrobial agents tested in disk diffusion assay. Penicillin and ampicillin resistance rates were signiϐican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
51
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 16 publications
(20 reference statements)
6
51
0
3
Order By: Relevance
“…The same result obtained by [37] detected a single amplicon of 173 bp of blaZ gene. Our results showed that all tested strains for mecA gene were positive for blaZ gene and this similar to [38] who noticed that all positive strains to mecA were also positive for blaZ gene and the presence of both genes was correlated to phenotypic beta-lactam resistance of S. aureus strains.…”
Section: Discussionsupporting
confidence: 90%
“…The same result obtained by [37] detected a single amplicon of 173 bp of blaZ gene. Our results showed that all tested strains for mecA gene were positive for blaZ gene and this similar to [38] who noticed that all positive strains to mecA were also positive for blaZ gene and the presence of both genes was correlated to phenotypic beta-lactam resistance of S. aureus strains.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, bovine multidrug resistant S. aureus strains could be zoonotic pathogens (Soares et al, 2012). Given that Vancomycin and oxacillin are important antibiotics for human, isolates.Our results indicated high resistance rate for oxacillin which is responsible for methicillin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing to species level would be critical in the event that it has effect on administration and treatment choices [23]. …”
Section: Discussionmentioning
confidence: 99%